Brain response to different message content of pictorial health warnings from tobacco packages: comparison between smokers and non-smokers using fMRI - Lee, Cheeh Hui (2018)
The effectiveness of the Pictorial Health Warnings Labels (PHWLs) from the tobacco packages in tobacco control remains controversial. To date, there is lacking of functional magnetic resonance imaging (fMRI) studies on the message content of the labels with different value emphasis. These values are the crucial components in the cigarette related decision making. In this study, the brain activation of the smokers and non-smokers from the young age group in response to PHWLs themes (Cosmetic Consequences “COS”, Endanger Others “EN”, Negative Lifestyle “NE” as well as Disease and Death “DD” were investigated. To ensure the adequacy of the labels in evoking desired affective states, an online normative rating questionnaire was completed by 100 respondents to obtain valence and arousal values for each PHWLs themes. One-way repeated measures ANOVA (p < 0.05) revealed that all PHWLs themes were rated significantly more unpleasant and arousing than the control (Natural “NA”) images, except NE on the arousal dimension. Followed by that, 10 smokers and 10 nonsmokers lied inside an MRI machine to view a series of images that categorized into different themes. Blood-oxygenated-level-dependent responses during the fMRI task were captured to examine the brain activation in response to the PHWLs themes between the groups in terms of spatial extent. As revealed from the random-effects analyses (2 x 5 mixed ANOVA) with Puncorrected < 0.001, a widespread of regions that associated with cognitive and affective functioning were recruited by smokers and non-smokers during the PHWLs viewing task, with or without taking the smoking status into consideration. Left middle temporal gyrus (associated with information integration) was activated when both groups viewing images of all themes. Regardless of the smoking status, visual related activation (i.e. inferior occipital gyrus (IOG), inferior temporal gyrus) were evoked by images of PHWLs themes with relatively similar extent while limbic related activation (i.e. right amygdala) were evoked by DD images in relative to NA images. Several new findings were noted. Firstly, greater brain activation wasobserved in regions associated salient stimulus detection (i.e. right inferior parietal gyrus, left middle frontal gyrus (MFG)) to COS images compared to EN images in smokers, social perception (i.e. left precentral gyrus (PG), left IOG) to EN images compared to NA images in both groups or regardless of smoking status, metaphor comprehension (i.e. left inferior frontal gyrus (IFG)) to NE images compared to EN images in smokers and strong emotional processing (i.e. right amygdala) to DD images compared to NA images irrespective of smoking status. Secondly, activation associated with emotional regulation (left PG) in response to EN and DD images compared to NA images was absent in smokers only. Thirdly, activation associated with salient stimulus detection and attentional processing in response to COS images compared to EN images was observed in smokers only. Fourthly, medial frontal activation that associated with self-related processing were exhibited by smokers more to COS and DD images in relative to other themes, with or without the consideration of smoking status. However, such activation was more responsive to COS than DD images for smokers. Fifthly, significant greater percent signal change (PSC) in the right IFG that associated with inhibitory control processing was observed when smokers and non-smokers viewing the NE images in relative to NA and COS images respectively as revealed from the dependent t-test and Wilcoxon-Signed Rank tests (p < 0.05) in the examination of brain activation in terms of intensity. Based on these new findings, several conclusions were made. Firstly, the main characteristics of each PHWLs theme might be reflected as the following: the salient feature of the COS images, the social aspect of smoking of the EN images, the symbolic nature of the NE images and the emotionally salient feature of the DD images. Secondly, desensitization towards the commonly known smoking risk (health issues and passive smoker) might have taken place in smokers only, underscoring the needs to address these smoking risk in a novel way. Thirdly, young smokers might have more concern about the smoking effect on their physical attributes than their health. The relevance of this message content type is supported with more attention givenby the smokers only to COS than EN images. These findings suggest that COS could be the ideal messages to reach to the young smokers effectively. Lastly, the inadequacy of the NE images in achieving effective message communication underscores the needs to refine the design of this message content type.